The Development and Validation of the Academic Spoken English Strategies Survey (ASESS) for Non-native English Speaking Graduate Students - Schroeder, Rui M. (Journal of International Students, 2016)
This study reports on the three-year development and validation of a new assessment tool—the Academic Spoken English Strategies Survey (ASESS). The questionnaire is the first of its kind to assess the listening and speaking strategy use of non-native English speaking (NNES) graduate students. A combination of sources was used to develop the questionnaire: literature reviews, pilot questionnaire results, feedback from pilot study participants, expert comments, and the author’s academic English learning journal. An exploratory factor analysis based on 384 respondents’ data was conducted to assess the construct validity. Cronbach’s alpha was 0.923, indicating high internal consistency. The study has made a significant contribution because data generated through the use of this questionnaire can provide valuable insights and pedagogical implications.